A survey on the impact of the COVID‐19 pandemic on motility and functional investigations in Europe and considerations for recommencing activities in the early recovery phase. Issue 7 (25th June 2020) - Tack, Jan; Schol, Jolien; Geeraerts, Annelies; Huang, I‐Hsuan; Mori, Hideki; Scarpellini, Emidio; Sinonquel, Pieter; Carbone, Florencia; Colomier, Esther; Geysen, Hannelore; Jandee, Sawangpong; Moonen, An; et al.
Abstract: Background: The COVID‐19 pandemic, declared by WHO on March 13, 2020, had a major global impact on the healthcare system and services. In the acute phase, the presence of the SARS‐CoV‐2 virus in the aerodigestive tract limited activities in the gastroenterology clinic and procedures to emergencies only. Motility and function testing was interrupted and as we enter the recovery phase, restarting these procedures requires a safety‐focused approach with adequate infection prevention for patients and healthcare professionals. Methods: We summarized knowledge on the presence of the SARS‐CoV‐2 virus in the aerodigestive tract and the risk of spread with motility and functional testing. We surveyed 39 European centers documenting how the pandemic affected activities and which measures they are considering for restarting these measurements. We propose recommendations based on current knowledge as applied in our center. Results: Positioning of catheters for gastrointestinal motility tests carries a concern for aerosol‐borne infection of healthcare workers. The risk is low with breath tests. The surveyed centers stopped almost all motility and function tests from the second half of March. The speed of restarting and the safety measures taken varied highly. Conclusions and Inferences: Based on these findings, we provided recommendations and practical relevant information for motility and function test procedures in the COVID‐19 pandemic era, to guarantee a high‐quality patient care with adequate infection prevention. Abstract : Overview of use of Personal Protective Equipment for motility studies during the COVID‐19 pandemic. Left: Donning procedure. Right: Doffing procedure.